1988
DOI: 10.1128/jcm.26.9.1818-1823.1988
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serologic assays for diagnosis of whooping cough

Abstract: An enzyme-linked immunosorbent assay (ELISA) for the immunoglobulin G (IgG), IgM, and IgA response to Bordetella pertussis filamentous hemagglutinin (FHA) and pertussis toxin (PT) and a neutralization test (NT) in a microplate tissue culture assay for neutralizing antibodies to PT were evaluated in paired sera from 90 patients with culture-confirmed pertussis. Eighty patients were children (age, <15 years), and 6 of 80 children had been immunized with three doses of diphtheria-tetanus-pertussis vaccine as infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
11
0
1

Year Published

1989
1989
1998
1998

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(15 citation statements)
references
References 14 publications
3
11
0
1
Order By: Relevance
“…The enzyme-linked immunosorbent assay (ELISA), using purified pertussis factors such as pertussis toxin (PT) or filamentous hemagglutinin (FHA), has recently been used extensively for epidemiological studies (8). This technique has proven to be reasonably sensitive and specific (1,3,13). It is generally concluded that a significant increase in specific anti-PT immunoglobulin G (IgG) or IgA and/or anti-FHA IgG or IgA in paired sera correlates with Bordetella pertussis infection.…”
mentioning
confidence: 99%
“…The enzyme-linked immunosorbent assay (ELISA), using purified pertussis factors such as pertussis toxin (PT) or filamentous hemagglutinin (FHA), has recently been used extensively for epidemiological studies (8). This technique has proven to be reasonably sensitive and specific (1,3,13). It is generally concluded that a significant increase in specific anti-PT immunoglobulin G (IgG) or IgA and/or anti-FHA IgG or IgA in paired sera correlates with Bordetella pertussis infection.…”
mentioning
confidence: 99%
“…Procedures currently available for the serodiagnosis of pertussis include the microagglutination test with whole bacteria (7), indirect enzyme-linked immunosorbent assay (indirect ELISA) with purified antigens (2,4,8,10), and Chinese hamster ovary (CHO) cell assay (3). Four pertussis-specific antigens are currently available; these are pertussis toxin (PT), filamentous hemagglutinin (FHA), pertactin, and fimbriae 2 and 3, among which PT is the most important antigen against Bordetella pertussis infection (1,9).…”
mentioning
confidence: 99%
“…Antibody against PT can be measured by ELISA and the CHO cell assay. Among these antibodies, immunoglobulin G (IgG) antibodies against PT detected by ELISA is the most useful for the serodiagnosis of pertussis (2,4). Although ELISA with these purified antigens has been successfully applied to the diagnosis of pertussis, the requirements for special equipment and techniques, as well as difficulties with technical reproducibility, limit its availability (8).…”
mentioning
confidence: 99%
“…Purified FHA and PT have been under intensive investigation for use as immunogens in experimental acellular pertussis vaccines (1, 14) and as antigens for the serodiagnosis of pertussis (2,4,(18)(19)(20). Because of meager antigen yields in the commonly used growth media (3,16) and the relatively complicated purification techniques, these antigens have been quite expensive and hard to obtain.…”
mentioning
confidence: 99%